2017
DOI: 10.36829/63cts.v4i2.355
|View full text |Cite
|
Sign up to set email alerts
|

Inhibición de los efectos coagulante, fosfolipasa A2 y proteolítico del veneno de Bothrops asper por plantas usadas tradicionalmente en Centroamérica

Abstract: Existen pocos estudios científicos que demuestren el valor terapéutico de las plantas en la medicina tradicional centroamericana para tratar el envenenamiento ofídico. En este estudio se evaluó la capacidad de los extractos etanólicos de nueve plantas de uso etnomédico en Centroamérica (Acacia hindsii, Aristolochia maxima, Bursera simaruba, Cissampelos pareira, Eryngium foetidum, Hamelia patens, Pimenta dioica, Piper peltatum y Sansevieria hyacinthoides) para inhibir el efecto coagulante del veneno de Bothrops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
2
0
2
Order By: Relevance
“…However, there is a lack of published information concerning the ethnobotanical use of P. dioica to treat snakebite envenoming. The work published by Castro et al (1999) reported that extracts from the leaves collected in Costa Rica completely neutralized the hemorrhagic activity induced by the venom of B. asper, which correlates well with the ability shown by the ethanolic extract of Guatemalan specimens to inhibit the proteolytic activity of the venom (Saravia et al, 2017). Ethnomedicinal uses of the plant and pharmacological activities found on its extracts may explain those findings, suggesting the potential usefulness of P. dioica in snakebite envenoming in Central America.…”
Section: Ethnopharmacology Of the Plants Studied In Guatemalamentioning
confidence: 57%
See 1 more Smart Citation
“…However, there is a lack of published information concerning the ethnobotanical use of P. dioica to treat snakebite envenoming. The work published by Castro et al (1999) reported that extracts from the leaves collected in Costa Rica completely neutralized the hemorrhagic activity induced by the venom of B. asper, which correlates well with the ability shown by the ethanolic extract of Guatemalan specimens to inhibit the proteolytic activity of the venom (Saravia et al, 2017). Ethnomedicinal uses of the plant and pharmacological activities found on its extracts may explain those findings, suggesting the potential usefulness of P. dioica in snakebite envenoming in Central America.…”
Section: Ethnopharmacology Of the Plants Studied In Guatemalamentioning
confidence: 57%
“…Giovannini & Howes, 2017; Küpeli et al, 2006;Paul et al, 2011;Saravia et al, 2017Saravia et al, , 2022 Akah, 1993;Hay, 2002;Owoyele et al, 2008;Pandith et al, 2012Pandith et al, , 2013Saravia et al, 2001 Giovannini & Howes, 2017;Jiménez-Suárez et al, 2016;Saravia et al, 2015Saravia et al, , 2017 complete inhibition of PLA 2 enzymatic activity (evaluated as indirect hemolysis) and proteolytic activities of B. asper venom. However, the extract also showed intrinsic anticoagulant activity, a property that might aggravate the hemostatic alterations induced by the venom in coagulation (Table 2) (Saravia-Otten et al, 2021).…”
Section: Anti-inflammatory Antibacterial Analgesic Treatment Of Scorp...mentioning
confidence: 99%
“…Al realizar el tamizaje fitoquímico obtuvieron: "todas las especies vegetales del estudio presentaron flavonoides, antocianinas, catequinas en su composición química, los taninos estuvieron presentes en cuatro de ellas" (Saravia, et al, 2017) (B. simaruba, E. foetidum, H. patens y P. dioica), mientras que las cumarinas se manifestaron en A. maxima (corteza), B. simaruba, C. pareira, H. patensy P. peltatum. La siguiente tabla resume los resultados alcanzados: Tabla 1.…”
Section: Tamizaje Fitoquímicounclassified
“…Concluyen (Saravia, et al, (2017) que "los extractos de P. dioica y E. foetidum inhiben efectivamente el efecto proteolítico del veneno de B. asper". También se identificaron metabolitos secundarios que podrían estar relacionados con su capacidad inhibitoria, el aislamiento de estos compuestos requiere más estudios, pues solo así se podrá determinar el mecanismo directo por el cual se ven inhibidas las actividades que ocasiona el veneno.…”
Section: Actividad Antioxidante Polifenoles Totales Y Tamizaje Fitoqu...unclassified